LEXICAL ATTRITION IN MULTILINGUAL LANGUAGE LEARNERS - Lilik Ulfiati (JAMBI-ENGLISH LANGUAGE TEACHING, 2022)
Multilingual language learners are facing various challenges of language attrition, both internally and externally. Lexical attrition is one of phenomena experienced by the learners since they can no longer do something which s/he had previously been able to do, and this loss of proficiency is not caused by deterioration of the brain due to age, illness or injury, but by changes in linguistic behaviour due to severance of the contact with the community in which the language is spoken (Smith, 2017). This article is trying to capture the studies of lexical attrition in the multilingual contexts and suggest several improvement strategies in experiencing the lexical attrition. This study is using content analysis to explore existing literature on lexical attrition in multilingual language learners over the last ten years. A summary of more than seventeen is provided along with the content analysis. The finding of these studies gives a significant contribution to the field of language attrition that focuses on practical analysis in learners or speakers points of view in the multilingual context. It shows that the limitation of understanding on lexical attrition concept from the local authorities in many educational settings have resulted in less efficient and effective language maintenance.